Galaxy evolution in groups: Transition galaxies in the IllustrisTNG simulations - Levis, Selene (2025)
The evolution of galaxies is significantly influenced by the environments they inhabit. While high-density regions, such as clusters of galaxies have been widely studied, the dynamics and quenching processes in intermediate environments remain less explored. These systems provide a valuable context for understanding the transition of galaxies from active star formation to quiescence. This study aims to characterise the astrophysical properties of galaxies in intermediate-mass galaxy groups (13.5≤log(M200/M⊙)≤13.7), with a focus on their evolutionary pathways and the key processes driving their transition through the green valley (GV) and green zone (GZ). Using the Illustris TNG300-1 hydrodynamical cosmological simulations, we classified galaxies based on their trajectories and environment into five categories: group galaxies (GRs), backsplash galaxies (BSs), recent infallers (RINs), infall galaxies (INs), and field galaxies (FGs). We examined their optical colours in the (u−r) -stellar mass diagram, specific star formation rates (sSFRs), gas fractions, and stellar mass evolution from z=0.5 to z=0. At z=0 , FGs dominate the blue cloud, while GRs show progressive reddening. BSs exhibit the highest fraction of green galaxies, highlighting their transitional nature, whereas RINs show a rapid quenching upon entering R200 . Our results reveal that the timing of group entry and environmental effects, such as gas depletion, play a critical role in galaxy quenching. Green BS and RINs follow distinct evolutionary tracks, with the latter undergoing more rapid changes due to later infall into more massive systems.